Abducens Palsy Due to Cerebral Venous Sinus Thrombosis in a Patient with Heart Failure - Cem Özgönül; Osman Melih Ceylan; Fatih Mehmet Mutlu (Türk Oftalmoloji Dergisi, 2015)
Cerebral venous sinus thrombosis has a wide spectrum of presentation. The clinical manifestation depends on the location of the thrombus, its rate of progression, and the extent of venous collateralization. In this case report, we present the findings of cerebral venous sinus thrombosis presenting with abducens palsy and papilloedema in a patient with heart failure, an unusual etiology for cerebral venous sinus thrombosis. (Turk J Ophthalmol 2015; 45: 179-181)